Impact and Control Measures of Subway Shield Tunnel Underpassing Ancient Buildings - HE Shengya; LI Hengyi; WANG Zhijie (Chengshi guidao jiaotong yanjiu)
[Objective] To clarify the impact of tunnel construction and operation in soft soil areas on ancient buildings, and formulate corresponding control plans, it is necessary to study the control of subway tunnel construction impact on ancient buildings. [Method] Taking Shenzhen Metro Line 3 under the Xiao′s Diaolou (watchtower) in Pingxi Community as an example, a large-scale three-dimensional calculation model is established to study the influence of tunnel construction and train vibration on the Diaolou structure. The control effects of pile-beam underpinning and foundation grouting reinforcement are compared, and the optimal control measures are determined. Combined with the on-site monitoring results, the feasibility of proposed control measures is verified. [Result & Conclusion] If no control measures are taken, the construction of subway tunnel may cause severe overall tilt of Diaolou. During operation periods, the horizontal vibration velocity at top of Diaolou caused by trains reaches 1.41 mm/s, failing to meet the control requirements. Upon foundation grouting reinforcement measures, the settlement value at top of Diaolou is only reduced by 17.5%, while the overall sinking problem of the Diaolou foundation can be basically solved after adopting pile-beam underpinning measures, with Diaolou’s vibration velocity reduced to 0.33 mm/s, and its structure maximum response stress is 30.39 kPa. According to on-site monitoring data, the Diaolou top settlement, Diaolou tilt rate and land subsidence after adopting pile-beam underpinning measures are 10 mm, 0.4‰ and 12 mm respectively, lower than the control values of 14 mm, 2.0‰ and 30 mm. When carrying out structural stability control in soft soil areas, pile reinforcement measures should be fully utilized, and the pile ends be certainly embedded to the effective bearing layer.